Grammatical Gender Inhibition in Bilinguals - Morales, Luis; Paolieri, Daniela; Bajo, Teresa (Frontiers in Psychology, 2011)
Inhibitory control processes have been recently considered to be involved in interference resolution in bilinguals at the phonological level. In this study we explored if interference resolution is also carried out by this inhibitory mechanism at the grammatical level. Thirty-two bilinguals (Italian-L1 and Spanish-L2) participated. All of them completed two tasks. In the first one they had to name pictures in L2. We manipulated gender congruency between the two languages and the number of presentations of the pictures (1 and 5). Results showed a gender congruency effect with slower naming latencies in the incongruent condition. In the second task, participants were presented with the pictures practiced during the first naming task, but now they were asked to produce the L1 article. Results showed a grammatical gender congruency effect in L1 that increased for those words practiced 5 times in L2. Our conclusion is that an inhibitory mechanism was involved in the suppression of the native language during a picture naming task. Furthermore, this inhibitory process was also involved in suppressing grammatical gender when it was a source of competition between the languages.